Some Properties of Luminal Sucrase and Sucrase-Isomaltase Complex in Rat Small Intestine - HOSOYA, Norimasa; ABE, Masako; MORIUCHI, Sachiko; YAMADA, Kazuhiko (Journal of Nutritional Science and Vitaminology, 1985)
Some properties of luminal sucrase4somaltase complex and the effect of luminal fluid on their complex were studied in rat small intestine. Luminal contents were collected by flushing the small intestine with the buffered solution. The enzyme activity was observed in luminal contents and intestinal mucosa. Sucrase and Isomaltase activities were located mainly in the intestinal mucosa. However, approximately 20% of sucrase and 10% of isomaltase activities of total small intestine were found in the luminal contents. A significant amount of sucrase without isomaltase activity, the molecular weight of which was estimated at about 140, 000 daltons, was found in the luminal supernatant of the distal intestine in addition to the complexed form of sucrase and isomaltase. The luminal sucrase and sucrase-isomaltase complex had similar properties such as Km values, optimal pH, molecular weights and antigenicity against anti sucrase-isomaltase antibody compared with brush border membrane-bound sucrase-isomaltase complex. Furthermore, the supernatant of the luminal contents of the ileum had a degradative effect on the isomaltase moiety of the purified sucrase-isomaltase complex and a free sucrase without isomaltase also appeared in vitro as observed in vivo. These results suggest that the sucrase-isomaltase complex is released into the intestinal lumen from the brush border membrane and that a luminal factor affects the degradation step of this enzyme as well as the biosynthesis of su-crase-isomaltase complex.